Free-volume correlation with mechanical and dielectric properties of natural rubber/multi walled carbon nanotubes composites. (October 2015) - Ponnamma, Deepalekshmi; Ramachandran, Renjith; Hussain, Shamima; Rajaraman, R.; Amarendra, G.; Varughese, K.T.; Thomas, Sabu
Graphical abstract: Abstract: The microstructure, mechanical strength, dielectric properties, Doppler broadening measurements and positron life time studies of the composites containing multi walled carbon nanotubes (MWCNTs) and natural rubber (NR) are investigated. The uniform distribution of MWCNTs in the elastomer medium is studied by Raman spectroscopy and the electron microscopy images show the composite's internal microstructure. Free volume sizes and interstitial mesopore sizes of the nanocomposites are determined by positron annihilation lifetime spectroscopy (PALS). PALS investigates the influence of the nanotubes in regulating the interphase nanoscale character. Strong interfacial interaction causes an apparent reduction of the free-volume fraction of NR probably by depressing the formation of free-volume holes in the interfacial region. The mechanical percolation and percolation observed from the dielectric measurements are correlated with the life time values. It is established that the sub-nano level free volumes and nano level structure of the composites have significant roles in regulating the mechanical properties.